Influence of Carbon Dioxide Fluctuation and Thermal Environment on Workability, Physiology and Psychology - CHIKAMOTO, Tomoyuki; MIMURA, Ryouto (E3S Web of Conferences, 2019)
Although carbon dioxide (CO 2 ) is a gas not perceived by human, extremely high concentration of CO 2 has an influence on the human’s health. High concentration of CO 2 also leads to lowering concentration ability and promoting drowsiness. It may also have an influence on productivity and learning efficiency of human. We conducted experiments to measure the amount of workability and the physiological and psychological response of the subjects. In the experiment, the concentration of CO 2 was set at the constant level at each case. And then, the concentration of CO 2 was changed to examine the physiological and psychological response. In the result of the experiment, the CO 2 concentration had the influence on productivity and working efficiency of human. Even if the CO 2 concentration is not so high, physiological condition of the human would be also affected.